Reconstruction's Lessons - Susan Carle (Columbia Journal of Race and Law)
In the current moment in the legal struggle for racial equality in the United States, the nation seems at risk of repeating its history. The Roberts Court has failed to fulfill its charge under the Reconstruction amendments to vigorously promote and enforce civil rights protections, and the other branches of government have proved ineffectual or unwilling to step into the breach. The racist far right is rising and the national electorate appears unable to organize in favor of racial justice priorities. In recognition of these partial analogies between conditions then and now, this Article mines the history of Reconstruction and its aftermath for lessons pertinent to the racial justice struggle today. It asks what lessons racial justice activists and legal scholars might glean from that history to help them grow their tally of gains and shrink their tally of losses despite today’s less than ideal legal and political conditions. What the history of Reconstruction teaches is that legal prescription and doctrinal manipulation alone will not bring about greater racial equality; having learned that lesson from Reconstruction’s history, today’s racial justice activists and scholars should direct their efforts towards exploring what new approaches might be effective despite today’s less than optimal legal and political conditions.